Optimizing Economics Learning Through the Utilization of Quizizz Digital Media at SMAN 14 Gowa - Nurwahida, Nurwahida; Supatminingsih, Tuti; Damasinta, Alfiana; Hisanan, Herawan; Salam, Supardi (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
The development of digital technology brings significant opportunities for improving the quality of learning in schools, including in Economics, a subject often considered abstract by students. This community service activity aims to improve the effectiveness of Economics learning through training in the use of digital media Quizizz for teachers and students at SMAN 14 Gowa. The activity was carried out through socialization of the Quizizz concept, training in question creation, mentoring in the use of live and assign modes, and direct practice by students in the form of group quizzes. The implementation methods included interactive lectures, demonstrations, andhands-on practiceThe results of the activity showed that teachers gained a better understanding of the use of Quizizz as a teaching and evaluation medium, demonstrated by their ability to create independent quizzes and utilize the automatic reporting feature. Students also demonstrated increased learning motivation, active participation, and understanding of economic concepts through a more interactive and enjoyable learning experience. This activity demonstrated that the integration of gamification-based digital media such as Quizizz can create a more adaptive, engaging learning process, and in accordance with the characteristics of the digital generation. Thus, the use of Quizizz can be an innovative alternative to improve the quality of Economics learning at the secondary school level.